MENINGKATKAN KEMAMPUAN MENULIS PERMULAAN DENGAN MENGGUNAKAN MAGIC WITHEBOARD BAGI ANAK TUNAGRAHITA SEDANG - Chori RGP, Asep Ahmad Sopandi, Yosfan Azwandi (Jurnal Penelitian Pendidikan Khusus, 2013)
This research background in the background by the findings in the field are special-ed students tunagrahita Bina Bangsa, Padang. Have problems writing, the results tulisanya not resemble the actual form letter. Helped to improve his writing skills using Magic Witheboard. This research Single Subject Research shaped with AB design. Analysis of the data using a visual chart to record the frequency of the number of letters in the letter written by the actual pattern. Observations concluded that the use of Magic Witheboard permulaaan can improve writing skills.